Developments in the Reform of China’s Banking and Financial Systems Commentary - Hongru, Liu (Columbia Journal of Asian Law, 1988)
A nation’s banking and financial institutions are intimately related to that nation’s evolving economic structure and development. Thus, banking and financial reform is of critical importance to China’s overall economic restructuring. Briefly stated, the People’s Republic of China has traditionally maintained a product-economy management system’ under highly centralized control, characterized by management in kind3 and mandatory planning. Under this type of centralized economic system, China’s banks have traditionally played the essentially passive roles of bookkeepers and cashiers, with the result that China’s banking and financial systems have long remained undeveloped. Nevertheless, significant reforms are cur- rently underway.